FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NASABAH MENABUNG DI BANK SUMSEL BABEL KCP TANJUNG SAKTI - Jepri Aris Munandar; Onsardi Onsardi ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2021)
This study aimed to determine affectin factors customers’ saving interest at Sumsel Babel Kcp Tanjung Sakti Bank. The data collection techniques of this study were observation, and questionnaire. The object of this study were customers of Sumsel Babel Kcp Tanjung Sakti Bank in 2019 with a total of 2855. The sample of this study was a non-probability sampling technique with purposive sampling with more than 100 customers. This study used the Slovin formula in sampling with an error rate of 10% and the sample in this study amounted to 97 people. This study used several data analysis techniques, namely instrument test, classical assumption test, respondent response analysis, classical assumption test, multiple linear regression analysis, determinant coefficient, and hypothesis testing. The results of the tests that have been carried out can be concluded that Knowledge (X_1), Products (X_2) and Promotion (X3) on the dependent variable savings interest (Y). It can be seen in the F test which states the value of F_count> Ftable, namely (163.654> 2.702 ) and (sig α = 0.000 <0.050), in other word that H_3 is accepted, meaning that simultaneously Knowledge (X_1), Product (X_2) and Promotion (X3) variables have a significant effect toward customers’ saving interest (Y) at Bank Sumsel Babel KCP Tanjung Sakti. Keywords: Products, Promotion, and Interest in Saving